If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y-1/3)=-1.2(2y-10)
We simplify the equation to the form, which is simple to understand
6(y-1/3)=-1.2(2y-10)
Reorder the terms in parentheses
+(+6y-2)=-1.2*(2y-10)
Remove unnecessary parentheses
+6y-2=-1.2+*(+2y-10+)
Reorder the terms in parentheses
+6y-2=+(-2.4y+12)
Remove unnecessary parentheses
+6y-2=-2.4y+12
We move all terms containing y to the left and all other terms to the right.
+6y+2.4y=+12+2
We simplify left and right side of the equation.
+8.4y=+14
We divide both sides of the equation by 8.4 to get y.
y=1.6666666666667
| 12y-21/4= | | -x+6y=16 | | 20cosX=-31.3229 | | 8d+4=2d | | 2x+41=83 | | 5x^3+36x+7=0 | | -12y-6x=3 | | x(14x+31)+15=0 | | -7a-2b+7+2b+5a= | | 39,41=120,84 | | (8x-3)-(7x-4)+(-5x+6)= | | 4x^3+12x^2-72x-160=0 | | 7x-28y=35 | | 7x(6x+1)=511 | | 9x+63=8x+59 | | log(9x^2)-log(x)=2 | | 7x+8=3x-24 | | 11x-2=-24 | | combine(8x-3)-(7x-4)+(-5x+6)= | | 3y-2y=1 | | 18=0.9(x-1) | | x+2x+4=21 | | -2/3s-1=56 | | 30=.666666667p | | 14T^2-3T-2=0 | | 2y^2-7y-1=0 | | 15-2y=20 | | 2x-16=180 | | X(12+x)=38 | | (7x-3)/(x-5)0 | | X^2+4x+4=2x+19 | | 0.75(2x-3)-.05(6-x)=1.5x+3 |